2022
DOI: 10.3389/pore.2022.1610506
|View full text |Cite
|
Sign up to set email alerts
|

Holliday Cross-Recognition Protein HJURP: Association With the Tumor Microenvironment in Hepatocellular Carcinoma and With Patient Prognosis

Abstract: Background: Hepatocellular carcinoma is the most common type of primary liver cancer, and it is associated with poor prognosis. It often fails to respond to immunotherapy, highlighting the need to identify genes that are associated with the tumor microenvironment and may be good therapeutic targets. We and others have shown that the Holliday cross-recognition protein HJURP can promote the proliferation, migration, and invasion by hepatocellular carcinoma cells, and that HJURP overexpression is associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…HJURP can participate in various cell proliferation-related pathways and promote the proliferation of tumor cells, such as HCC. This is consistent with the fact that HJURP requires CENPA to bind to centrioles during telolobe/early G1 phase, which ensures normal chromosome segregation during mitosis 16 . However, there is no sufficient and effective evidence for the pathogenesis of HJURP in a variety of cancers, and it remains unclear about whether HJURP plays a role in TME, cell cycle progression, tumor treatment and prognosis through a common molecular mechanism in the context of immunocytological action.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…HJURP can participate in various cell proliferation-related pathways and promote the proliferation of tumor cells, such as HCC. This is consistent with the fact that HJURP requires CENPA to bind to centrioles during telolobe/early G1 phase, which ensures normal chromosome segregation during mitosis 16 . However, there is no sufficient and effective evidence for the pathogenesis of HJURP in a variety of cancers, and it remains unclear about whether HJURP plays a role in TME, cell cycle progression, tumor treatment and prognosis through a common molecular mechanism in the context of immunocytological action.…”
Section: Introductionsupporting
confidence: 86%
“…GO enrichment analysis of HJURP and these gene functional partners revealed that they have immune-related functions. Clustering dendrogram of the top-ranked GO biological processes (GO-BP) showing major pathways such as cellular detection biotic interferon-gamma, neuron death oxidative stress, immune assembly phagocytosis bioprocesses, gland migration morphogenesis duct and interleukin-1 cysteine-type production endopeptidase 16 .
Figure 2 HJURP showed changes in protein expression levels associated with interval progression in G1, S, and G2 phasesa ( A ).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the principal components analysis (PCA) (orthogonal rotation) method in the "IOBR" package 35 to construct a scoring system to evaluate the levels of 44 collagen molecules in SKCM patients and named it Col_Score. The Col_Score formula is Col_Score = ∑(PC1+PC2).…”
Section: Col_score Evaluationmentioning
confidence: 99%
“…Aberrant expression of chromatin regulators (CRs) has a major impact on immune responses. For example, HJURP has been associated with immune cell infiltration and immune checkpoint expression in hepatocellular carcinoma and clear cell renal cell carcinoma (8)(9)(10). HMGB3 was a member of a family of chromatin-binding proteins that can modify DNA structure to facilitate transcription factor binding (11,12).…”
Section: Introductionmentioning
confidence: 99%